The Importance of Tourism in Regional Economic Development: A Time-Series Analysis - MEYER, Daniel Francois; BRUYN, Chané de; MEYER, Natanya (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017DO - 10.14505//jemt.v8.4(20).08, 2017)
Tourism is more often than not overlooked in its ability to alleviate poverty and the promotion of regional economic development. The aim of this study was to assess the importance of tourism in regional economic development and to gain a deeper understanding of the Vaal Triangle’s tourism profile which includes its potential and obstacles in tourism development. The study region included Emfuleni and Metsimaholo Municipal areas which forms the Vaal Triangle region, located in the southern portion of Gauteng, South Africa. Secondary data from 2001 to 2015 was obtained from Global Insight. The data was analysed with the use of a pooled panel cointegration model. The results from the statistical analysis showed that there is indeed a positive relationship between tourism, regional economic development and economic growth. In addition, a qualitative analysis was conducted by means of semi- structured interviews with key regional tourism stakeholders in the study region to gain in-depth knowledge on the opportunities and constraints facing the tourism industry. The results indicated that there are many underutilized resources and that cooperation between the community, local government and tourism organisations need to be improved. In order to achieve sustainable tourism development and economic growth, increased awareness should be created and with the correct policy measures tourism holds many opportunities for the Vaal Triangle region and other developing regions.